2020
DOI: 10.3389/fpsyt.2020.00019
|View full text |Cite
|
Sign up to set email alerts
|

Five Applications of Narrative Exposure Therapy for Children and Adolescents Presenting With Post-Traumatic Stress Disorders

Abstract: Narrative exposure therapy (NET) is an individual therapeutic approach that has an emerging evidence base for children. It was initially trialed with refugee and asylum seeking populations, in low, middle and high-income settings, utilizing either lay or professional therapists. The results of treatment trials for PTSD in refugee children with NET (or the child "KIDNET" adaptation) demonstrates how this is an effective intervention, is scalable and culturally dexterous. This paper describes, in five cases from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 40 publications
0
52
0
Order By: Relevance
“…40 The approach uses creative methods, such as using flowers and stones to indicate hot and cold memories, and placing them along a piece of string or rope (representing the timeline/age of the person); such approaches show promise with young people and adults, with systematic review evidence showing moderate effect sizes. 41,42 A review of quasi-experimental and qualitative studies 43 found the evidence base for interventions in refugees to be generally poor, but recommended that mental health interventions must address immediate needs and concerns before focusing on past traumas, and consider social groups, group therapy and building a social network in conjunction with pharmacotherapy and individual counselling. The ordering of interventions should be driven by the narrative emphasis given by the patient for immediate concerns, and only then can the clinician's judgement of priorities be carefully explained, negotiated and located within the patient's preferred approach to recovery.…”
Section: Innovations For Eco-social Narrative Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 The approach uses creative methods, such as using flowers and stones to indicate hot and cold memories, and placing them along a piece of string or rope (representing the timeline/age of the person); such approaches show promise with young people and adults, with systematic review evidence showing moderate effect sizes. 41,42 A review of quasi-experimental and qualitative studies 43 found the evidence base for interventions in refugees to be generally poor, but recommended that mental health interventions must address immediate needs and concerns before focusing on past traumas, and consider social groups, group therapy and building a social network in conjunction with pharmacotherapy and individual counselling. The ordering of interventions should be driven by the narrative emphasis given by the patient for immediate concerns, and only then can the clinician's judgement of priorities be carefully explained, negotiated and located within the patient's preferred approach to recovery.…”
Section: Innovations For Eco-social Narrative Interventionsmentioning
confidence: 99%
“… 40 The approach uses creative methods, such as using flowers and stones to indicate hot and cold memories, and placing them along a piece of string or rope (representing the timeline/age of the person); such approaches show promise with young people and adults, with systematic review evidence showing moderate effect sizes. 41 , 42 …”
Section: Innovations For Eco-social Narrative Interventionsmentioning
confidence: 99%
“…A recent case series on the applications of NET identified additional functional improvements following NET including reduced self-harm, decreased anger outbursts and reduced aggression, improvement in school attendance, reduced substance misuse, and the development of positive relationships, in addition to decreased PTSD symptoms (Fazel et al ., 2020). In this paper, young people were reported to have chosen NET over other trauma-focused therapies as they shared a preference for talking about all of their experiences, that it was helpful to know what was coming next, and that they wanted to create the lifeline.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, young people were reported to have chosen NET over other trauma-focused therapies as they shared a preference for talking about all of their experiences, that it was helpful to know what was coming next, and that they wanted to create the lifeline. The authors also identified that NET may have a lower cognitive load than other trauma-focused therapies, as it aims to describe the original memory rather than potentially complex and abstract meanings attributed to the event, and may be more acceptable for clients with additional needs, such as autism spectrum conditions (Fazel et al ., 2020). Recent evidence has also highlighted how interpreters can be used to deliver NET to encourage timely access to therapy for refugees in Western countries (Lambert and Alhassoon, 2015; Lely et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A modified version, KIDNET, has been developed and used with children from age 7 (Neuner et al, 2008). Research studies have demonstrated the effectiveness of NET/KIDNET for reducing anxiety and PTSD symptoms in adults and children who have experienced single or multiple traumas, including children with autism spectrum disorders and those with intellectual impairments (Fazel et al, 2020; Karam et al, 2019). NET/KIDNET is a standardized form of trauma-based therapy, designed to facilitate the process of converting fragmented autobiographic memories into coherent personal narratives.…”
mentioning
confidence: 99%